“Real” Places in Marguerite Duras’s Wartime Paris - Jennifer Willging (Studies in 20th & 21st Century Literature, 2011)
In the four autobiographical narratives in Marguerite Duras’s La Douleur (1985) The War (1994), over one hundred proper place names appear. While these place names all refer to real places, the relationship between these signifiers and their actual geographical referents is mediated, first by their signifieds—the reader’s mental constructs of the places mentioned—and further by their appearance in a text that necessarily creates its own, non-material world. Yet this essay argues that in this uncharacteristically realist text Duras works hard to create the illusion that the Paris there is in fact Occupied Paris, the real city in which she lived out the experiences recounted in her text. She does this, in large part, by indicating the location of each scene with meticulous precision, thus grounding the stories, quite literally, in a geographically and historically situated reality. While many of these sites are among the best-known, and literal, lieux de mémoire ‘sites of memory’ of the Paris of the Second World War, the mention of more obscure places might appear gratuitous. Yet it is precisely in their gratuity, that such details become essential elements of the forceful effet de réel ‘reality effect’ created in the text.
Keywords: autobiographical narratives; Marguerite Duras; La Douleur; the War; signifier; geographical referent; non-material; Occupied Paris; alternate reality; geographically situated reality; historically situated reality; lieux de mémoire; sites of memory; Second World War; Paris; World War II; effet de réel; reality effect